Review of the largest species group of the New World seed beetle genus Sennius Bridwell (Coleoptera: Chrysomelidae), with host plant associations - Viana, Jéssica Herzog; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2013)
Sennius Bridwell is a New World genus of Bruchinae. Most species are placed in eight groups. In this study the species of the S. abbreviatus group are reviewed based on characters of the external morphology and the male genitalia. The group includes 14 species, two of which are new: Sennius abbreviatus (Say, 1824), S. bondari (Pic, 1929), S. durangensis Johnson & Kingsolver, 1973, S. lawrencei Johnson, 1977, S. lebasi (Fåhraeus, 1839), S. leucostauros Johnson & Kingsolver, 1973, S. lojaensis (Pic, 1933), S. medialis (Sharp, 1885), S. nappi Ribeiro-Costa & Reynaud, 1998, S. rufomaculatus (Motschulsky, 1874), S. transversesignatus (Fåhraeus, 1839), S. trinotaticollis (Pic, 1930), S. vivi sp. nov. and S. flinte sp. nov. The S. abbreviatus group differs from other groups by the pattern of sclerites and the shape of the internal sac of the male genitalia, and has three subgroups, defined here. The lectotype of S. lebasi is designated. New host plant records are presented for S. lojaensis and S. transversesignatus, and new distribution records for S. lawrencei, S. lojaensis and S. trinotaticollis.